VD_FINDINFO HC / 2011 / 206 vom 15. März 2011 - VD Tribunal cantonal (2011)
JUGEMENT DE DIVORCE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE | 276 CC, 285 al. 1 CC, 92 CPC, 117 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH)